Economic and political liberalizations - Francesco Giavazzi; Guido Tabellini (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper studies empirically the effects of and the interactions amongst economic and political liberalizations. Economic liberalizations are measured by a widely used indicator that captures the scope of the market in the economy, and in particular of policies towards freer international trade (cf. Sachs and Werner 1995, Wacziarg and Welch 2003). Political liberalizations correspond to the event of becoming a democracy. Using a difference-indifference estimation, we ask what are the effects of liberalizations on economic performance, on macroeconomic policy and on structural policies. The main results concern the quantitative relevance of the feedback and interaction effects between the two kinds of reforms. First, we find positive feedback effects between economic and political reforms. The timing of events indicates that causality is more likely to run from political to economic liberalizations, rather than viceversa, but we cannot rule out feedback effects in both directions. Second, the sequence of reforms matters. Countries that first liberalize and then become democracies do much better than countries that pursue the opposite sequence, in almost all dimensions.
Keywords: O1; O11; 330; political liberalization; democracy; economic reform; Deregulierung; Makroökonomischer Einfluß; Politische Reform; Demokratisierung; Schätzung; Welt